Modeling Tasik Harapan As A Flood Retention Pond. - Teh, Su Yean; Koh, Hock Lye; Chan, Ngai Weng; Md Ismail, Ahmad Izani (USM, 2006)
Past philosophy that sought maximum conveyance of storm water at an individual site by the most rapid possible elimination of exccess surface water after a rainfall is no longer a prefered choice in the best management practice in flood control (ASCE, 1979).